시스템다이내믹스를 이용한 국내 기성금 제도 현황 분석 및 개선방안 제시 - 공공건설분야를 중심으로 - 박문서; 이정훈; 이현수; 황성주; 김수영; Park, Moon-Seo; Lee, Jeoung-Hoon; Lee, Hyun-Soo; Hwang, Sung-Joo; Kim, Soo-Young (한국건설관리학회 논문집, 13(1), 2012)
Recently construction companies' capital condition has been aggravated due to low profit, fierce competition and market contraction. For this reason, the companies rely on public construction projects that protect construction fee by regulations. Despite these regulations, problems regarding progress payment are constantly happening. Also, insufficient analysis on interaction between contractors makes policy making difficult. Thus, in this study, interaction between contractors are quantitatively determined according to delay of application and payment based on current public construction regulations on construction stage. A system dynamics model is used, which analyzes the problems based on an interaction between contractors, and solutions for progress payment application and payment delay are suggested according to the research results. 최근 건설경기 위축으로 건설 계약자들의 치열한 수주 경쟁 및 수익성 저조에 따른 경영악화 현상이 심각한 수준에 이르고 있다. 이러한 상황에서 많은 건설관계자들은 "국가계약법"에 의해 공사비를 보호받을 수 있는 공공건설사업에 대한 의존도가 높아지고 있다. 그러나 이러한 법률적 규정이 존재함에도 불구하고 기성금 신청 및 지급과 관련된 문제가 지속적으로 발생하고 있으며, 이를 해결하기 위해 제시되는 대부분의 방안이 계약관계자간의 상호 영향도를 충분히 반영하지 못하고 있어 이를 정책적으로 반영하는데 어려움이 있다. 이에 본 연구에서는 공공건설사업 시공단계의 기성금 신청 및 지급에 대한 현행 규정제도를 바탕으로 신청 지연 및 지급지연에 따른 계약 관계자들의 상대적 영향도를 정량적으로 파악하고자 한다. 이를 위해 상호 관계성에 관한 지식을 바탕으로 통합적 시각에 따른 현상 분석이 가능한 시스템다이내믹스 모델을 통한 연구를 바탕으로 기성금 신청 및 지급 문제를 해결하기 위한 방안을 제시하였다.